Teachers’ professional development system of Singapore - Turekeeva Alfiya (International Consortium of Education and Culture Research Studies, 2019)
This article deals somecontemporary experiences with the Singaporean educational system, especially in teachers’ professional development. Furthermore, there are some analysis of national institution and the centralized process of the educational system of Singapore. Moreover, there is described not only the mechanism of choosing the future professionals between the graduators of HEI, and their scientific expansion, but also the usage of the modern pedagogical and IC technologies at the lessons by teachers